VALUATION OF THE LIABILITY STRUCTURE BY REAL OPTIONS - HELLER, DAVID (JOHN WILEY, 2022)
The valuation of the liability structure can be determined by real options because the shares of a company can be regarded as similar to the purchase of a financial call option. Therefore, from this perspective, debt can be viewed as the sale of a financial put option. As a result, financial analysts are able to establish different valuations of a company, according to these two financing methods. Valuation of the Liability Structure by Real Options explains how the real options method works in conjunction with traditional methods. This innovative approach is particularly suited to the valuation of companies in industries where an underlying asset has high volatility (such as the mining or oil industries) or where research and development costs are high (for example, the pharmaceutical industry). Integration of the economic value of net debt (rather than the accounting value) and integration of the asset volatility are the main advantages of this approach.